Analyst forecast accuracy and earnings management - Zaini Embong; Hosseini, Leila (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper investigates the reciprocal or endogenous relationship between earnings management and analyst forecast accuracy. Earnings number is one of the most referred information especially in relation to investment decision-making. Financial analysts use earnings number and its trend in coming up with their forecast. The quality of earnings reported hence may affect the accuracy of forecast made by analysts. Quality of reported earnings is often indicated by earnings management. One of the motivations to manage earnings is to meet or beat analyst forecasts. If analysts failed to account for earnings management, it is possible that earnings manipulation in the previous year may mislead analysts and affect forecast accuracy for current and/or future years. Thus, relationship between earnings management and forecast accuracy could be endogenous or reciprocal, where managers react upon analysts’ forecasts and analysts use reported earnings to make forecast. Previous research on this area assume earnings management and forecast accuracy as exogenous variables. This study on the other hand incorporates the reciprocal relationship between analyst forecast accuracy and earnings management in examining whether analysts can detect earnings management. The relationship between earnings management and analyst forecast accuracy of 110 firms listed on Main board of Bursa Malaysia from 2007 to 2012 is analyzed using dynamic panel system Generalized Method of Moments (GMM) estimator. The year 2007 to 2012 is chosen because this represents the period of convergence from MASB to MFRS. Result indicates that meeting or beating the forecast is one of the incentives for earnings management although not a strong incentive. On the other hand, earnings management significantly influence forecast accuracy, indicating that somehow, analysts trust the reported earnings. This study adds to the literature by addressing the possible endogenous and dynamic relationship between earnings management and analyst forecast accuracy.